Interdisciplinary management of head and neck vascular anomalies: clinical presentation, diagnostic findings and minimalinvasive therapies - Sadick, Maliha; Hülse, Carl Roland; Lange, Bettina; Henzler, Thomas; Schönberg, Stefan; Sadick, Haneen (European journal of radiology open, 2017)
Objectives: Vascular anomalies are included in the 30 000 rare diseases worldwide affecting less than 5/10 000 people. Depending on their morphology and biological properties, they can cause varied disorders with organ involvement. Almost 60% of vascular anomalies have a predilection for the head and neck region in children. Clinical and scientific effort to establish interdisciplinary management concepts for vascular anomalies is increasing worldwide. Methods: Especially in the head and neck region, clinical impairment and organ dysfunction is associated with cosmetic issues that may represent a physical and psychological issue for the patient. Correct diagnosis, based on clinical presentation and symptoms, is a prerequisite for appropriate therapy, ranging from conservative management to a spectrum of minimally invasive treatment options. We searched PubMed for German and English language published data until December 2016 with focus on clinical studies, review articles and case reports on vascular anomalies with a focus on the head and neck region. Results: The last ISSVA update in 2014 has contributed to a better understanding of vascular anomalies, classifying them in vascular tumors and vascular malformations. The predominant representatives of vascular tumors are congenital and infantile hemangiomas. Infantile hemangiomas have the ability of spontaneous regression in more than 80%. Patients with symptomatic growing hemangiomas with ulcerations, bleeding complications and restriction of hearing, swallowing disorder, impairment of vision, or cosmetic dysfigurement require treatment. Therapies include oral propanolol, transcatheter embolization and surgery. Vascular malformations tend to progress with patientś age and are subdivided in slow flow and fast flow lesions. Symptomatic slow flow lesions, e.g. venous and lymphatic malformations, benefit from percutaneous sclerotherapy. Fast flow lesions, as arteriovenous malformations, are rare but undoubtedly therapeutically the most challenging vascular anomaly. Depending on location and size, they may require multiple transcatheter embolization procedures for successful occlusion of the AVM. Conclusions: This review provides knowledge on the current ISSVA classification of vascular anomalies, their clinical presentation, diagnostic evaluation and minimally invasive therapy options to encourage the establishment of a comprehensive interdisciplinary management for head and neck vascular anomalies.